A Study on the Aesthetic Criteria of Modern Architectural Structures in Developing Countries with Emphasis on Bionic Architecture - Adel Bakhshi Balkanloo (هنر اسلامی, 2020)
The skeletal form of the structure is undoubtedly closely related to the form of the carrier structure. However, the relationship between structural design and architectural design can yield many forms. Structures, as the foundation of buildings in all countries, provide a suitable platform for architectural design. In modern architecture, new tools and designs are used, including biotic architecture. In this research, the combined method (descriptive and analytical-qualitative-historical) is applied to study and the collection and analysis is accomplished based on library studies. The results of this study show that bionic architecture is in fact a creative tool to achieve effective and efficient goals. Observance of legal and logical principles in building structures provides the ground for new architecture and appropriate visual vision. The bionic perspective on architectural design takes place in different areas. At times the aesthetic aspect of the project, and at other times the structure, climate issues and the functional solutions have been the goal of the designer of this field. With the results obtained in the analysis of case studies, it can be determined that the interaction effects of structure and architecture from the perspective of bionic architecture are significant and structure and architecture interact closely with each other and the avoidance of any of the mentioned categories can cause irreparable damage. Research aims: 1. Investigating the interactions of structure and architecture and how they interact with each other 2. Investigating the status of modern architecture and the use of natural instruments (bionic architecture) as a symbol (aesthetics) Research questions: 1. What is the role of structures on modern architecture and aesthetic standards in developing countries? 2- How can the physical quality of space be expanded by using the new technology of the third millennium and the harmonization of structure and architecture?